Pengembangan Industri Kreatif di Panti Asuhan Miftahunnajah Banguntapan Bantul Yogyakarta Berupa Pendampingan Pembuatan Produk Kreatif dari Bahan Limbah Konveksi (Kain Perca) - Yasrin Zabidi (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2018)
Miftahunnajah Orphanage is a community group that organizes pesantren education for orphans. For that purpose, the orphanage management needs a lot of operational expenses in the organization of education and to fulfill the needs of the students santri. So far, the funds used for operations are mostly dependent on donors from donors. The santri in this orphanage have good potential to be developed in order to be more economically independent and not only rely on donor donations or existing funders. While in the neighborhood around the orphanage many resources that can be raised to be developed in the form of creative industries. One of the existing resources is the existence of scrap wastes from small convection industry in Yogyakarta. Creativity and innovation santri-santri Miftahunnajah orphanage needs to be developed in order to capture the opportunities that exist in the vicinity. The solution to solve the problem of lack of creativity and innovation of the santri at Miftahunnajah Orphanage is to provide guidance for business counseling. Therefore in the activities of Community Service T.A. 2017/2018, the proposer conducted advisory activities to nurture and guide the Orphanage Miftahunnajah in making creative products and innovations from waste patchwork materials that exist in the surrounding environment to be a creative product and can be marketed so as to support the orphanage economy and become the Orphanage economically independent. The steps undertaken in the Community Service activities are as follows: 1) Conducting a survey to find out the condition of Orphanage Miftahunnajah in Wonocatur Banguntapan area, 2) Conducting data of creative industries appropriate for guidance / mentoring, 3) Conducting business assistance in the form of guidance of creating creative and innovative products from waste materials that can be developed at Miftahunnajah Wonocatur Banguntapan orphanage. The result of this community service activity is children at Miftahunnajah Orphanage can make creative and innovative product from waste material of patchwork.